PERBANDINGAN UJI EFEKTIVITAS EKSTRAK ETANOL DAUN JAMBU AIR (Syzygium aqueum) DENGAN PENGENCER TWEEN DAN PEG TERHADAP MORTALITAS LARVA Aedes aegypti - Geraldo Zikri Azmi Ramadhan; Retno Sintowati; Nurhayani, Nurhayani; Yusuf Alam Romadhon (Bajang Institute, 2024)
The Aedes aegypti mosquito is the main vector for transmitting the Dengue virus which causes Dengue Hemorrhagic Fever (DHF). Synthetic larvicide is a method commonly used to break the life cycle of the Aedes aegypti mosquito. Water guava leaves contain phenols (flavonoids), saponins, tannins, alkaloids and polyphenols, which can be used as natural larvicides. The aim of this research was to determine the effectiveness of ethanol extract of water guava leaves (Syzygium aqueum) with TWEEN and PEG diluents on the mortality of Aedes aegypti larvae, as well as a comparison of the effectiveness of the two. This type of research is an experimental laboratory with a posttest only control group design using observation techniques for the control and treatment groups.There were 3 control groups consisting of 1 positive control group (abate) and 2 negative control groups (TWEEN and PEG diluent). There were 4 treatment groups, namely TWEEN and PEG diluents which were added with water guava leaf ethanol extract with concentrations of 1.5% or 2%. The Aedes aegypti larvae used as samples were instars III to IV. Mortality of Aedes aegypti larvae for the 7 groups was recorded every 6 hours for 24 hours. Larval mortality data is not normally distributed and the variance is not homogeneous, so the mean difference test uses non-parametric Kruskal-Wallis statistics. The results of this test showed a real difference (sig.p<0.005), so it was continued with the Post-Hoc Mann Whitney test to determine more specific differences (effectiveness). The results of the Mann Whitney test showed that the ethanol extract of water guava leaves (Syzygium aqueum) with TWEEN and PEG diluent was effective on the mortality of Aedes aegypti larvae (sig.p<0.005), with the same level of effectiveness (sig.p>0.005), so it can be concluded that the ethanol extract of water guava leaves (Syzygium aqueum) with TWEEN and PEG diluents are equally effective against the mortality of Aedes aegypti larvae